PERILAKU TABUNGAN: KASUS PERBANDINGAN NEGARA-NEGARA ASEAN DAN NEGARA INDUSTRI MAJU 1989 -1996 - Faried Wijaya Mansoer (Journal of Indonesian Economy and Business (JIEB), 1998)
Understanding the nature of savings behavior is critical in designing policies to promote saving and investment. Usually, government of developing countries addopt saving policies of developed countries, particularly United States, without adjusted with their economy and politics circumstances. This study aims at examining the difference in saving behavior in ASEAN versus industrial countries. The ASEAN countries used are Indonesia, Malaysia, Philipina, Thailand, and Singapura. As expected, the estimation result shows that saving behavior in developing countries differ with developed countries, that decribed by sign and value of parameter of independent (exogenous) variabel. Interest rates have positive impact for saving behavior in developed countries, but negative impact in developing countries. This result doubt hyphotesis of Mckinnon and Swan about financial deregulation.